PENDAPATAN USAHA PERIKANAN BAGAN APUNG DI NEGERI TULEHU KABUPATEN MALUKU TENGAH - Sakina Wally; Dionisius Bawole; Yolanda Marla Tania Nangkah Apituley (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Fishing using a floating lift net contributes a positive impact on the fishermen of Tulehu village, but problems faced by fishermen in fishing often affect their income. This study aims to analyze the income of the floating lift net business in Tulehu village. The results showed that the number of fishing activities for floating lift net during the non-fishing season were 55 trips and during the fishing season 138 trips. Fixed costs incurred during the non-fishing season was Rp32,971,175 and in the fishing season was Rp13,294,150, while variable costs during the non-fishing season was Rp19,361,175 and during the fishing season was Rp25,042,200. Based on the costs incurred, the floating lift net business earns an average profit of Rp59,045,620 during the non-fishing season and Rp247,597,600 during the fishing season. Research should be continued with an analysis of the financial feasibility of the business, so it can be seen whether the business is feasible or not.